Photoinduced Oxidation Reactions of the Pendent Macrocyclic Complexes: Al(Iii) Phthalocyanine and Ni(Ii) Annulene Mechanistic Considerations - Matsuhiro-Yamamoto, B; Matsuhiro-Yamamoto, B (Elsevier Ltd, 2016)
The goal of the work was to expand the understanding of the photoinduced redox reactions of the Al(III) sulfonated phthalocyanine, HOAlIIItspc, and Ni(II) tertramethyldibenzotetraazaannnulene, [NiII(tmdbTAA)], as components of polymeric structures in which poly(ethyleneimino) and poly(isobutyl-alt-maleate) are the respective backbones of poly(HOAlIIItspc) and poly([NiII(tmdbTAA)]). Saccharide and flavonoid glycosides form adducts that quench the photo-generated oxidizing radicals in the case of poly(HOAlIIItspc) with rate constants ≈ 1 × 104 s-1, largely independent of reductant structure. The charge-separated intermediate, CS, in the case of poly([NiII(tmdbTAA)]) shows greater reactivity with the saccharides and flavonoid glycosides, particularly with the flavonoid glycoside rutin where the rate constant is 2.7 × 106 s-1. While phthalocyanine-centered radicals in poly(HOAlIIItspc) were reduced by dAMP (adenosine-5-monophosphate) and CT-DNA, energy transfer with these reagents competed with the formation of the CS intermediate in poly([NiII(tmdbTAA)]). A study of the intensity of the upper conversion luminescence (λem < 500 nm), modulated by the concentration of dAMP suggests that this is attributed to the formation of adducts of poly([NiII(tmdbTAA)]) with dAMP that affect the deactivation of the electronically excited Ni(II) tetraazaannnulene pendants before the formation of the CS intermediate. © 2016 Elsevier Ltd.